An inquiry into the workplace learning of small food-based manufacturing industry in Selangor - Hanis Mai'sarah, Mohd Fadzil (Universiti Malaysia Sarawak, 2019)
The purpose of this study is to explore the workplace learning behavior of small ownermanager of food-based manufacturing industry in Selangor. It extends the knowledge in the workplace learning and small organization, contribute to policy maker / HR practitioner and help the existing and potential entrepreneurs. There were 3 research questions in this study, (i) How do the owner-manager of small food-based manufacturing industry learn in their workplace?; (ii) What are the factors that trigger workplace learning among owner-manager of small food-based manufacturing industry?; (iii)What are the barriers and challenges of workplace learning for the owner-manager of small food-based manufacturing industry? The study used a qualitative approach and there were 10 informants that participated in this study. The informants fulfilled two criteria for the study, (i) the owner-manager or business partner is an active person in the food-based manufacturing and (ii) the business must be at least 3 years of establishment. Semi structured interview and document analysis were used to collect the data. The data was analyzed using content analysis. Finding revealed that, almost all of the informants practiced structured (training) and unstructured types of learning (self-directed learning, observation, trial and error, problem solving, social network and family). The informants identified several factors that trigger workplace learning: (i) business factor (different customer needs, problem solving and sustainability), (ii) environment factor (family support, competitors and exposed environment) and (iii) personal factor (social media and decision Maker). Meanwhile, the barriers and challenges for the owner-manager to learn is (i) personal factor (lack of motivation and time-constraints) and (ii) job factor (heavy workload). The implication and recommendation of the study were discussed.